The Unique Tradition of Timber Shophouses in Sarawak. Issue 2 (4th May 2022) - Ting, John Hwa Seng
ABSTRACT: Rendered, whitewashed masonry shophouses are a common vernacular type in Southeast Asia's urban heritage districts. There were, however, parallel vernacular timber shophouse traditions where brick was not available. In much of nineteenth-century Sarawak, local timbers were used for structural frames, joinery, wall cladding and roofing shingles. Even when bricks became available, timber approaches were not completely replaced. Although timber shophouses are now uncommon in Southeast Asia's large cities due to modernisation and development, outstation Sarawak is a rich repository of pre-1960 examples. Shophouse development in Sarawak was non-linear, with modern and vernacular approaches pursued contemporaneously. While timber construction was necessary due to the lack of bricks outside of the capital, Kuching, it is also because of the government's unique approach to governance, hygiene, building regulation and approaches to representation before World War Two. Despite their ubiquity and longevity in many parts of Malaysia, timber shophouse types have generally been left out of national architectural historiographies This paper begins to address this gap by interrogating the architectural development of shophouses in Sarawak, within the context of the history of the type's architecture and construction in Malaysia and Singapore.